Determination of Financial Risk Tolerance among Different Household Sectors in Sri Lanka - Heenkenda, Shirantha (Asian Economic and Social Society, 2015)
This study examined the financial risk of tolerant behavior at the household level with particular emphasis on different household sectors in Sri Lanka. The analysis measured, the household willingness to take financial risk or risk tolerance based on a questionnaire survey. Financial risk tolerance was measured with the help of a likert-scale and a composite index was developed using the values for the answers. The study used descriptive statistics and also the one-way analysis of variance (ANOVA) test to compare the risk tolerance between the three main household sectors, i.e. urban, rural and estate. The effects of socio-econ-demographic factors upon financial risk tolerance of households were investigated using Tobit regression analysis. The results revealed that a majority of respondents exhibited an above average (high) risk tolerance as a whole and demonstrated significant differences in risk tolerance preferences of households at sectoral level. The results indicate that gender, age, education, occupational status, income, income diversification, distance to a financial institute and financial literacy are significant in the determination of the financial risk tolerance. The findings provide inputs for designing policies for the development of the financial markets in the Sri Lankan context.
Keywords: Financial risk tolerance; risk assessment; financial planning